Strategi Komunikasi Interpersonal Orang Tua dalam Meningkatkan Minat dan Bakat Anak di Kelurahan Suka Raja, Kecamatan Medan Maimun, Kota Medan - Dina Anzani; Ika Ramadhani Panjaitan; Isnaini Harahap; M. Rio Fani (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
Communication strategy is the capital used in dealing with the community in Sungai Deli, Sukaraja urban village. as well as interpersonal communication strategies of parents to their children. Meanwhile, education is a positive contribution used in carrying out communication activities. The analytical technique involved usesqualitative reasoning that directs children as the target of reasoning. students become communicators who bridge children as communicants to find goals and develop existing interests and talents.Changing the paradigm of parents to get their children to go to school is an effort that is expected to be an output of awareness of the importance of education.